2014
DOI: 10.11604/pamj.2014.17.116.1837
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of cardiovascular admissions at Nnamdi Azikiwe University Teaching Hospital Nnewi, South East Nigeria

Abstract: IntroductionCardiovascular disease (CVD) is one of the top killer diseases in the world sparing neither developed or developing countries. The study was carried out to determine the pattern of cardiovascular admissions at Nnamdi Azikiwe University Teaching Hospital Nnewi South East Nigeria.MethodsThe study was a retrospective study covering the period January 2007 to December 2009. SPSS version 13 software was used to analyze data.Results537 (15%) patients were admitted into the study out of 3546 patients {fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
7
10
1
Order By: Relevance
“…Moreover, as life expectancies rise due to economic development, CVDs prevalence is increasing, presenting new pressure on already struggling health systems. We found that hypertension, the major risk condition for CVDs, was most prevalent among the three CVDs risk conditions studied in our review [9,28,32]. However, a high prevalence of diabetes and overweight/obesity was reported as well [9,15,23,37].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, as life expectancies rise due to economic development, CVDs prevalence is increasing, presenting new pressure on already struggling health systems. We found that hypertension, the major risk condition for CVDs, was most prevalent among the three CVDs risk conditions studied in our review [9,28,32]. However, a high prevalence of diabetes and overweight/obesity was reported as well [9,15,23,37].…”
Section: Discussionmentioning
confidence: 91%
“…Major findings reported in the review. ,13,14,[17][18][19][20][21][27][28][29][30][33][34][35][36]39,40,42,44,46,[50][51][52][53][54][55][56][57] Significant in some group 28[8,9,12,[14][15][16]20,[23][24][25][26][27]29,31,32,[36][37][38][39][40][41][42]45,47,48,…”
mentioning
confidence: 99%
“…All discrepancies the selection of studies were resolved through discussion or with the arbitrage of a third investigator. A total of 35 studies were included in this review [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] . A summary of the selection process is presented in the Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…It is commoner between the third and fifth decade of life when the individuals are in the prime of their life. The mean age ranges from 36.5 to 61.5 years (Figure 2A) [15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In high-income countries, it is commoner in the seventh decade of life.…”
Section: Age At Presentationmentioning
confidence: 99%